Prevalence of low back pain among handloom weavers in West Bengal, India. (October 2014) - Durlov, Santu; Chakrabarty, Sabarni; Chatterjee, Arijit; Das, Tamal; Dev, Samrat; Gangopadhyay, Somnath; Haldar, Prasun; Maity, Santi Gopal; Sarkar, Krishnendu; Sahu, Subhashis
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Handloom is one of the oldest industries in India, particularly in West Bengal, where a considerable number of rural people are engaged in weaving. Objectives: The purpose of this study was to evaluate the prevalence of low back pain among the handloom weavers in India. Methods: A modified Nordic Musculoskeletal Disorder Questionnaire and Oswestry Low Back Pain Disability Questionnaire along with a body part discomfort scale were administered to handloom weavers (n = 175). Working posture of the participants was assessed using the Ovako Working Posture Analysis System (OWAS). Results: Sixty eight per cent of the participants reported suffering from low back pain, making it the most prevalent disorder in our sample. Analysis of the Oswestry Low Back Pain Disability Questionnaire data revealed that among those with low back pain (n = 119), 2% had severe disabilities, 46% had moderate disabilities, and 52% had minimal disabilities. Statistical analyses revealed a positive significant association between the intensity of pain in the lower back and an increased number of years of work experience (P<0·05). Conclusions: The study underlines the need for further research regarding the postural strain of weavers and also suggests the implementation of ergonomic design into weaver workstations to minimize the adverse effect of their current working postures. Improving upon the weaver's work-posture could improve their quality of life.